(untitled) (Journal of Nepal Physical Society, 2016)
We have studied the electronic and magnetic properties of double perovskites Nd2MgIrO6 by means of full-potential linearized augmented plane wave (FP-LAPW) method based on density-functional theory (DFT). For the exchange-correlation potential, generalized gradient approximation (GGA) has been used. Based on our DFT calculations, Nd2MgIrO6 is found to have an antiferromagnetic (AFM) ground state. The material shows Mott-Hubbard type insulator, which is observed to occur due to strong correlation in Nd-4f and Ir-5d states in addition to large crystal distortion, observed in the system. Strong hybridization between O-2p, Ir-5d and Nd-4f electrons are observed from the density of states findings. Our results shows that the 5d electrons of Ir hybridize strongly with O-2p states close to the Fermi level giving rise to the insulating state with a Mott-gap of 0.9 eV in Nd2MgIrO6. Our study suggests that the total magnetic moment reduces to 5.0 μB per formula unit as a result of itinerant super-exchange rather than the exchange interaction involving individual ions of Nd and Ir atoms. Journal of Nepal Physical Society Vol.3(1) 2015: 50-54